Desenvolvimento e acoplamento por deslizamento vertical de dispositivos microfluídicos colorimétricos e eletroquímicos baseados em papel usando suporte impresso em 3D para detecção multiplexada de metais - Silva Neto, Habdias de Araujo (2020)
As the world population increases at a rate of 80 million per year, this behavior requires an increase on demand for essential resources such as food, fuel and fiber, causing agribusiness companies to intensify the exploitation of natural resources. However, they negatively affect the environmental compartments of the region, such as fluvial systems with metal pollutants. Thus, various analytical methods have been reported to detect and quantify metals in environmental samples, such as atomic absorption spectroscopy, coupled plasma mass spectrometry and coupled plasma atomic emission spectrometry. However, these detection systems require a long training time and high financial investment, which make research on environmental pollutants in developing countries difficult. Here, we report for the first time the integration of a paper-based electrochemical and colorimetric device (ePAD and μPAD) through vertical sliding coupling on three-dimensional printed support for multiplexed detection of Zn, Cd, Pb, Fe, Ni and Cu in a water sample from the Meia Ponte River. It was possible to manufacture 90 μPADs and 140 ePADs using a chromatographic and vegetal paper, respectively. In addition, the cost price of the device was c.a. 0.03 USD (R$ 0,1), considering the paper, conductive inks, and plastic material. The combination of the electrochemical and colorimetric detection methods of the proposed analytical system did not statistically interfere with the signal of simultaneous detection of metals (significance level <95%), enabling the multiplexed detection of six metals.During the proof-of-concept, the method showed a fast analysis time (10 min), good analytical frequency (36 analyzes per hour) and detection limits were 1.46 (Zn), 1.26 (Cd) and 0.51 (Pb ) μg L-1 for electrochemical detection and 0.14 (Fe), 0.33 (Ni) and 0.15 (Cu) mg L-1 (colorimetric detection). Furthermore, the proposed method successfully demonstrated the detection of metals in Meia Ponte River water samples (range 16 to 786 μg L-1), in the recovery studies (76 to 121%) and when compared with the atomic absorption spectroscopy method (significance level of 95%). Thus, the integration of ePAD and μPAD by vertical sliding was efficient for multiplexed analysis of heavy metals and can be exploited to monitor metallic pollutants in industrial process residues, by environmental inspection agencies and in river water samples.